Bolivia : Request for Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper examines Bolivia's Request for a Stand-By Arrangement (SBA). The Bolivian authorities have focused their efforts on restoring economic and social stability, strengthening the banking and corporate sectors, and establishing the basis for sustained growth. In support of their economic program for 2003, the authorities have requested an SBA equivalent to 50 percent of quota (SDR 86 million). At the same time, the authorities continue to develop a broader set of medium-term structural reforms, for which they plan to seek support through an arrangement under the Poverty Reduction and Growth Facility as soon as possible.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet